Incidence of steroid modified tinea in tertiary care centre Lucknow - Chaudhary, Savita; Shukla, Priyanka; Gupta, Khushboo; Paliwal, Gaurav (International Journal of Research in Dermatology, 2018)
Background: Rampant use and abuse of topical steroids has led to increase in number of cases of superficial dermatophytosis of skin, nail and hair. In most of the cases they are resistant to topical as well as oral antifungals even after prolong course of treatment. Our study aims to analyse epidemiological and microbiological profile of steroid modified tinea (SMT). Methods: Clinically diagnosed tinea patients with history of usage of topical steroids were included in our study. Detailed history was taken and clinical examination along with KOH mount and culture was done. Results: 980 patients were screened of which 550 patients with history of using topical steroids were included in our study. Most common age group was 20 to 29 years with male: female of ratio approximately 3:1 and disseminated form was the most common variety. KOH mount was positive in 76% cases and culture was positive in 72% cases. Most common species came out to be T. Mentagrophytes followed by T. rubrum. Among non-dermatophyte group, Candida was the commonest. Conclusions: There is rise in incidence of dermatophytosis, especially steroid modified one and cases of disseminated tinea are rising.